A taxonomic survey of Caridean and Penaeid shrimp in Lapinig Bay, Northern Samar. - Juarez, Bridgette M.; Varona, Gracia F. (Bridgette M. Juarez, 2018)
There are no recent inventory on caridean and penaeid shrimp species in the Samar islands. Furthermore, no studies related to taxonomy of all caridean and penaeid shrimp have been conducted in Lapinig Bay, Northern Samar. Thus, this study is aimed to survey the marine, and brackish caridean, and penaeid shrimp present in the municipality. Caridean and penaeid shrimps were collected in the different areas of the bay with varying depth and salinity from January to March 2018.
A total of 143 individual caridean and penaeid shrimps belonging to 19 species from four families were collected and identified in Lapinig Bay, Northern Samar. Metapenaeus ensis was the most abundant making up to 14.6% of the total shrimp count. Superfamily Caridea had the most number of species present with a majority of its individuals found near the river. Penaeid shrimps were more abundant in the subtidal zones than in the intertidal.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.